Energy system benefits of combined electricity and thermal storage integrated with district heating - Lund, Rasmus (International Journal of Sustainable Energy Planning and Management, 2021)
In the development towards a smart and renewable energy systems with increasing supply of electricity from fluctuating sources there is an increasing need for system flexibility. In this context the role and need for grid-level electricity storage is debated. Ideally, there would not be a need for storage, but the alternative system flexibility solutions may not cover all the flexibility needs, which will leave a potential for storage of electricity. In this study a compressed heat energy storage (CHEST) is assessed. It combines electricity and thermal storage in one system and can simultaneously benefit electricity and district heating systems. In a technical energy system analysis with the energy system of Germany as a case, a CHEST system is analyzed in different configurations with and without district heating integration. The results indicate that electrochemical storage is more effective than CHEST if district heating integration is not assumed. However, if district heating integration is assumed, CHEST can be more effective in reducing primary energy supply. This applies for district heating based on electrified heat sources, whereas in district heating supplied by combined heat and power plants and fuel boilers, CHEST do not show more effective.